Using a 3D integrated stereoscopic system to investigate the biomechanics of evasive sidestepping: Implications for ACL injuries - Lee, M.; Lay, B.; Lloyd, D.; Bourke, P.; Alderson, J. (Journal of Science and Medicine in Sport, 2011)
Purpose: Sidestepping is a context specific perceptual-motor skill commonly performed in team sports to evade opponent(s), but has never been investigated in conditions resembling game situations. This study examined selected trunk and lower body kinematics, kinetics, and muscle activation of high-level (HL) and low-level (LL) soccer players, during sidestepping to evade projected, three-dimensional (3D) stereoscopic defender(s). These comparisons were made with traditionally used two-dimensional planned and unplanned arrow stimuli. Implications for anterior cruciate ligament (ACL) injury prevention were discussed. Methods: A customised integrated stereoscopic system captured the 3D trunk and lower limb kinematics, and activation of 8 knee muscles, of 15 HL and 15 LL soccer players during the sidestepping tasks. The visual stimuli consisted of a one-defender scenario (1DS), two-defender scenario (2DS), arrow-planned condition (AP), and arrow-unplanned condition (AUNP). Temporal constraints imposed by the stimuli for sidestepping performance increased in the following order: AP, 1DS, 2DS, AUNP. A kinematic model was used in conjunction with force plate data to investigate knee valgus loading. Post-processed electromyography data were grouped into knee flexors and extensors to form co-contraction ratios. Muscles were also grouped into medial or lateral groups to form co-contraction ratios, depending on their ability to counter externally applied varus or valgus moments. Dependent variables were submitted to a 4 x 2 (stimulus x skill) mixed design ANOVA. Results: Stimuli significantly affected all measurements (P < 0.05). Placement of the support step prior to footstrike, peak frontal plane trunk flexion during stance, and peak knee valgus moments increased in accordance with stimuli imposed temporal constraints. At footstrike, push-off foot placement and hip abduction were similar in the 3D defender scenarios, suggesting an overarching influence of stimuli imposed spatial constraints. Muscle activation levels were similar across stimuli conditions. In the 2DS, the shift from a flexor dominant co-contraction strategy in pre-contact toward extensor dominance in weight-acceptance commenced earlier for the HL compared with the LL players. High-level players exhibited decreased hip abduction and knee valgus moments in the 2DS. Conclusion: Visual cueing affected sidestepping biomechanics. Sidestepping biomechanics of the HL and LL players only differed in the 2DS, due to the presence of visual-perceptual constraints resembling game situations, and the level of stimuli complexity. Using 3D stimuli to investigate sidestepping in a controlled environment addresses both the visual-perceptual and motor components of the manoeuvre. Such an approach has been suggested to improve the efficacy of ACL injury prevention models.